Ireland - Cox, Ronald C. (Civil engineering heritage., 1998)
Covers the areas of Ulster in the north through to Munster in the south, Leinster in the east and midlands and Connaught in the west. Aimed at both those with a civil engineering background and the general reader, this book describes some of the achievements of such famous names as Alexander Nimmo William Barrington, Charles Langor, and others.